3.5-GHz radiofrequency electromagnetic radiation promotes the development of Drosophila melanogaster. (1st February 2022) - Wang, Yahong; Jiang, Zhihao; Zhang, Lu; Zhang, Ziyan; Liao, Yanyan; Cai, Peng
Abstract: With the rapidly increasing popularity of 5G mobile technology, the effect of radiofrequency radiation on human health has caused public concern. This study explores the effects of a simulated 3.5 GHz radiofrequency electromagnetic radiation (RF-EMF) environment on the development and microbiome of flies under intensities of 0.1 W/m 2, 1 W/m 2 and 10 W/m 2 . We found that the pupation percentages in the first 3 days and eclosion rate in the first 2 days were increased under exposure to RF-EMF, and the mean development time was shortened. In a study on third-instar larvae, the expression levels of the heat shock protein genes hsp22, hsp26 and hsp70 and humoral immune system genes AttC, TotC and TotA were all significantly increased. In the oxidative stress system, DuoX gene expression was decreased, sod2 and cat gene expression levels were increased, and SOD and CAT enzyme activity also showed a significant increase. According to the 16S rDNA results, the diversity and species abundance of the microbial community decreased significantly, and according to the functional prediction analysis, the genera Acetobacter and Lactobacillus were significantly increased. In conclusion, 3.5 GHz RF-EMF may enhance thermal stress, oxidative stress and humoral immunity, cause changes in the microbial community, and regulate the insulin/TOR and ecdysteroid signalling pathways to promote fly development. Graphical abstract: Image 1 Highlights: Simulating the most representative 3.5 GHz RF-EMF band of 5G in China. We study the long-term effects of 3.5 GHz RF-EMF on flies' development. The microbial community may participate in the development under long-term RF-EMF. It provides a reference for the hidden health effects of RF-EMF.